Psychosocial Factors Related to Purchasing Decision Behavior under the Influence of Key Opinion Leaders among Undergraduate Students - Kongtraipop, Vaewan; Sakdapat, Naksit (The Periodical of Behavioral Science, 2023)
This study is a comparative study using the interactionism model. It aims to identify significant indicators and predict the volume of psychological and situational factors related to purchasing decision behavior under the influence of key opinion leaders among undergraduate students. The study’s sampling group is 846 undergraduate students, selected by multi-stage sampling. The study found that attitudes towards purchasing decision behavior under the influence of key opinion leaders (r = 0.575, p < .01). The multiple regression analysis found psychological traits, psychological states and situational factors can predict the purchasing decision behavior under the influence of key opinion leaders of the sampling group by 41.09%; the best predicting factor are attitudes towards purchasing decision behavior under the influence of key opinion leaders and basic of marketing. The high-risk groups include undergraduate female students, low-grade undergraduate students, and young undergraduate students. The results of this research suggest guidelines for the development of purchasing decision behavior under the influence of key opinion leaders of undergraduate students.